2021
DOI: 10.1002/ceat.202000477
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Functionalization of Graphene for the Enhancement of Thermophysical Properties in Nanofluids

Abstract: Covalent functionalization of graphene nanoparticles by autoclave, reflux-condensation, and microwave-assisted methods was performed. Nanofluids prepared by acidic functionalized graphene exhibit a higher dispersion stability than raw graphene. The thermal conductivity of nanofluids obtained by the microwaveassisted method was higher than with other functionalization methods, and a signifcant maximum thermal conductivity enhancement compared to deionized water was achieved. Microwave-assisted thermochemical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…40 Furthermore, the electrolyte concentrations in the phosphate buffer were optimized to ensure the most suitable ratio for the experiment. 41 For EIS, we employed a frequency response analyzer to measure the system's impedance across a range of frequencies, specifically from 100 kHz to 10 MHz.…”
Section: Synthesis Of Catalystsmentioning
confidence: 99%
“…40 Furthermore, the electrolyte concentrations in the phosphate buffer were optimized to ensure the most suitable ratio for the experiment. 41 For EIS, we employed a frequency response analyzer to measure the system's impedance across a range of frequencies, specifically from 100 kHz to 10 MHz.…”
Section: Synthesis Of Catalystsmentioning
confidence: 99%
“…Acidic functionalization has great promise for GO nanoparticles since it enhances the nanofluid's dispersion stability and thermal conductivity. 19 Irani et al 20 reported amine-functionalized GO and methyldiethylamine nanofluid for improving the CO 2 and H 2 S adsorption efficiencies of amine solution. They reported a high adsorption capacity of 16.2 and 17.7% of CO 2 and H 2 S, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are several methods for the chemical functionalization of GO, but the most common is a combination of acids and alkalis. Acidic functionalization has great promise for GO nanoparticles since it enhances the nanofluid’s dispersion stability and thermal conductivity . Irani et al reported amine-functionalized GO and methyldiethylamine nanofluid for improving the CO 2 and H 2 S adsorption efficiencies of amine solution.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these varieties of nanoparticles were integrated into fluids which include water and oil in ethylene glycol. Gold (Au), silver (Ag), and other nanoparticles were investigated due to their superior chemical, electrical, and optical properties in nanoscale 25–34. Eastman et al 35 found that copper oxide nanoparticles will give up to 65 % improvement in thermal conductivity of nanofluids for several industrial applications.…”
Section: Introductionmentioning
confidence: 99%